Aspirin-Exacerbated Respiratory Disease: Update on Pathogenesis and Desensitization - White, Andrew A.; Stevenson, Donald D. (Seminars in Respiratory and Critical Care Medicine, 2012)
Aspirin-exacerbated respiratory disease (AERD) is a unique syndrome of airway inflammation that frequently occurs in patients with nasal polyposis, chronic sinusitis, and asthma. These patients tend to have progressive and recalcitrant sinus disease requiring frequent surgical intervention and in many cases systemic corticosteroids. Much about the pathogenesis of AERD remains unclear, but environmental factors likely play a prominent role in its development. Avoidance of aspirin or nonsteroidal antiinflammatory drugs (NSAIDs) is imperative in the initial counseling of these patients. Because most of the exposure to these medications is available over the counter, most patients will experience a significant respiratory reaction to full therapeutic doses of seemingly innocent NSAIDs. Although the history of a reaction to aspirin or another NSAID is a very important part of making the diagnosis, the gold standard remains an observed aspirin challenge. Given the prevalence and usefulness of aspirin and NSAID therapy in primary care clinics, an accurate diagnosis should be made in all patients. Desensitization is an effective treatment option for many patients. Recent advances have made this procedure considerably safer and outpatient aspirin desensitization is now the standard of care.
Keywords: aspirin; nasal polyps; chronic sinusitis; asthma; nonsteroidal antiinflammatory drugs